Comparison of Human Adipose-Derived Stem Cells Isolated from Subcutaneous, Omental, and Intrathoracic Adipose Tissue Depots for Regenerative Applications. (20th December 2013) - Russo, Valerio; Yu, Claire; Belliveau, Paul; Hamilton, Andrew; Flynn, Lauren E.
Abstract : A broader understanding was sought regarding the influence of specific adipose tissue depots on the isolated adipose-derived stem cell (ASC) populations through a systematic comparison of donor-matched abdominal subcutaneous fat and omentum, and donor-matched pericardial adipose tissue and thymic remnant samples. Results suggest that depot selection is an important factor to consider when applying ASCs in tissue-specific cell-based regenerative therapies, and also highlight pericardial adipose tissue as a potential new ASC source. Abstract: Adipose tissue is an abundant source of multipotent progenitor cells that have shown promise in regenerative medicine. In humans, fat is primarily distributed in the subcutaneous and visceral depots, which have varying biochemical and functional properties. In most studies to date, subcutaneous adipose tissue has been investigated as the adipose-derived stem cell (ASC) source. In this study, we sought to develop a broader understanding of the influence of specific adipose tissue depots on the isolated ASC populations through a systematic comparison of donor-matched abdominal subcutaneous fat and omentum, and donor-matched pericardial adipose tissue and thymic remnant samples. We found depot-dependent and donor-dependent variability in the yield, viability, immunophenotype, clonogenic potential, doubling time, and adipogenic and osteogenic differentiation capacities of the ASC populations. More specifically, ASCs isolated from both intrathoracic depots had a longer average doubling time and a significantly higher proportion of CD34 + cells at passage 2, as compared with cells isolated from subcutaneous fat or the omentum. Furthermore, ASCs from subcutaneous and pericardial adipose tissue demonstrated enhanced adipogenic differentiation capacity, whereas ASCs isolated from the omentum displayed the highest levels of osteogenic markers in culture. Through cell culture analysis under hypoxic (5% O2 ) conditions, oxygen tension was shown to be a key mediator of colony-forming unit-fibroblast number and osteogenesis for all depots. Overall, our results suggest that depot selection is an important factor to consider when applying ASCs in tissue-specific cell-based regenerative therapies, and also highlight pericardial adipose tissue as a potential new ASC source.